Unraveling Cultural Practices and Sharia Economic Law in The Seaweed Trading System Of Kuala Stabas, Lampung - Pradikta, Hervin Yoki; Wazier, Rawan Ba; Nofika, Yenda; Muhammad, Hasanuddin (Institut Agama Islam Negeri Metro, 2024)
Buying and selling are essential economic activities integral to fulfilling daily needs. In the community of Kuala Stabas, Pesisir Barat Regency, Lampung, Indonesia, a unique system for trading seaweed using plastic bags without prior weighing is prevalent. The legality of this system under Sharia economic law remains unclear. This study aims to address this research gap by evaluating the legitimacy of the seaweed trading system using plastic bags from the perspective of Sharia economic law while also examining the local wisdom inherent in the practices of the Lampung community. This field research employs a qualitative descriptive approach, gathering primary data through interviews with key informants and supplementing it with secondary data. The uniqueness of this study lies in its in-depth analysis of local practices that have been scarcely studied. Findings indicate that the practice of trading seaweed using plastic bags in Kuala Stabas is lawful and permissible under Sharia economic law, as it aligns with the principles, requirements, and conditions of trade in Sharia, including Aqidain, Sighat (ijab qabul) and Ma'qud 'alaih. This research significantly contributes new insights into the local trading dynamics within the framework of Sharia economic law, enriching the existing literature and providing a foundation for further research.